(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Fungal diseases are serious complications in the treatment of leukemia patients and are linked to a high morbidity and mortality rate. Therefore, a correct definition of the risk level of fungal infections helps to improve strategies for the use of an antifungal prophylactic regimen. In the current study; we compared the prevalence of fungal infections pre and during chemotherapy in patients newly diagnosed with leukemia at Tishreen University Hospital in Lattakia, Syria. We investigated the risk factors for fungal infections in these patients during chemotherapy. Fungal infections diagnosis relied on both clinical symptoms and culture results on selective media (sabouraud dextrose agar and potato dextrose agar). We included fifty leukemia patients in this study (19 ALL, 14 AML, 12 CLL, and 5 CML). Fungal infections appeared in 11 patients (22%) before starting chemotherapy, all of these infections were of the genus Candida. While these infections appeared in 30 patients (60%) during chemotherapy, 48% were Candida, 10% were Rhizopus, and 2% were Aspergillus. Our results showed that the difference was significant in the percentage of fungal infections between pre-chemotherapy and during chemotherapy (p-value = 0.0001). While using the chi-square test or Fisher exact test, we found statistically significant differences between the two groups classified according to the incidence of fungal infections during chemotherapy in terms of smoking (p = 0.01), corticosteroid therapy (p = 0.0001), and the combination of the two previous risk factors (p = 0.0001), but there were no statistically significant differences between the two groups in terms of gender (p = 0.2), age (p = 0.1), and type of leukemia (p = 0.073).